The CLAVATA1 receptor-like kinase requires CLAVATA3 for its assembly into a signaling complex that includes KAPP and a Rho-related protein. - Trotochaud, A E (1999)
The CLAVATA1 (CLV1) and CLAVATA3 (CLV3) genes are required to maintain the balance between cell proliferation and organ formation at the Arabidopsis shoot and flower meristems. CLV1 encodes a receptor-like protein kinase. We have found that CLV1 is present in two protein complexes in vivo. One is approximately 185 kD, and the other is approximately 450 kD. In each complex, CLV1 is part of a disulfide-linked multimer of approximately 185 kD. The 450-kD complex contains the protein phosphatase KAPP, which is a negative regulator of CLV1 signaling, and a Rho GTPase-related protein. In clv1 and clv3 mutants, CLV1 is found primarily in the 185-kD complex. We propose that CLV1 is present as an inactive disulfide-linked heterodimer and that CLV3 functions to promote the assembly of the active 450-kD complex, which then relays signal transduction through a Rho GTPase.